Politics in the implementation of technology strategy. - Finkelstein, Marc-Elliott (IE University, 2021)
A significant managerial issue, organizations exhibit large variance in the implementation of their technology strategies. There is an extant theory gap at the intersection of politics and technology strategy implementation. Inductive, exploratory case study research was conducted at three different Canadian organizations to explore the linkage between politics and technology strategy implementation failure. It was found that six factors contributed to this variance: manner of performance recognition, organizational alignment of activities, mission/vision statement achievability, process transparency, governance complexion and sophistication in technology strategy development. While the factors were expressed differently among the organizations, the political activity enabled by these six factors influenced the implementation variance significantly, ranging from nearly no implementation variance to more than 100% implementation variance. Therefore, in the relationship between these variables and technology strategy implementation, there is an identifiable intermediate, dependent variable, political behaviour, which expresses a strong, linear, monotonic, positive relationship with the six independent variables. The variable political behaviour has a strong, linear, monotonic, negative relationship with the second dependent variable, technology strategy implementation achievement. Departing from extant studies, the most ostensibly significant factors were mission statement achievability, representative governance structure, and process transparency, which collectively set out the existential direction of the organization, empowered individuals to act for the organization and not in self-interest, and shone a light on all areas of the organization so that political actions were subject to the Spotlight Effect to the extent possible. In the reduction of political behaviour, technology strategy achievement was increased.
Política en la implementación de estrategia tecnológica.
Las organizaciones muestran una gran variabilidad en la implementación de sus estrategias tecnológicas, lo que supone un reto de gestión considerable. Existe un vacío  teórico en la intersección entre la política y la implementación de la estrategia tecnológica. Se ha llevado a cabo un estudio de caso inductivo y exploratorio en tres organizaciones canadienses diferentes para explorar la relación entre la política y el fracaso en la implementación de la estrategia tecnológica. Se ha descubierto que había seis factores que contribuían a esta variabilidad: la forma de reconocimiento del rendimiento, la alineación organizativa de las actividades, la viabilidad de la declaración de misión/visión, la transparencia del proceso, la complexión de la gobernanza y la sofisticación en el desarrollo de la estrategia tecnológica. Aunque los factores se expresaron de forma diferente entre las organizaciones, la actividad política posibilitada por estos seis factores influyó significativamente en la variabilidad de la implantación, que osciló entre una variación de implantación casi nula y una variación de implantación superior al 100%. Por tanto, en la relación entre estas variables y la implementación de la estrategia tecnológica, existe una variable intermedia y dependiente identificable, el comportamiento político, que expresa una relación fuerte, lineal, monótona y positiva con las seis variables independientes. La variable comportamiento político tiene una relación fuerte, lineal, monótona y negativa con la segunda variable dependiente, el logro de la implementación de la estrategia tecnológica. A diferencia de los estudios existentes, los factores más ostensiblemente significativos fueron la viabilidad de la declaración de misión, la estructura de gobierno representativa y la transparencia de los procesos, que en conjunto establecen la dirección existencial de la organización, facultaron a los individuos para actuar en favor de la organización y no en interés propio, y arrojaron luz sobre todas las áreas de la organización para que las acciones políticas estuvieran sujetas al Efecto Foco en la medida de lo posible. Al reducirse el comportamiento político, aumentó la consecución de la estrategia tecnológica.
Keywords: Technology strategy; Organizational politics; Technology implementation; Implementation failure; Innovación Tecnológica; Política Social; Gestión Administrativa; 1206.03 Análisis de Errores